Jaipongan Creative Music: from Local Expression to Global Phenomenon - Ismet Ruchimat (Pascasarjana ISBI Bandung Conference Series, 2025)
This paper discusses the development of West Javanese folk performing arts, which in this case is represented by Jaipongan, namely a type of dance and music performance that developed in the early 1970s. Jaipongan's creative historical journey from the beginning to the present is not only shown from its music and dance aspects, but it is also shown from its development, existence and influence abroad. These study based on theories of history, sociology, ethnomusicology and musical creativity. By using literature review methods, interviews and while the author was one of the composers at Jugala from 1993 until now, it can be concluded that the roots of creativity in West Javanese folk performances during the New Order era until now are represented by Jaipongan. Keyword: Jaipongan; History; Creativity; World Music